Fiscal outcomes and price effects of imposing duty - HUTSUL, Inna (Scientific journal «World of Finance», 2019)
Introduction. The formation of the revenue part of the budget is an important kind of activity of any state including Ukraine. Nowadays taxes are not only the main source of filling the state budget, but also a financial regulator of production. The development of the system of imposition of customs duty is urgent for Ukraine; the system which would include an extensive system of customs payments, because in addition to fiscal functions they regulate exportimport operations and ensure the economic security of the state. The purpose. The purpose of the article is to investigate theoretical and organizational principles for imposing a duty, to determine its fiscal role and price effects for the society. Results. The essence, functions and fiscal role of a duty have been determined. The peculiarities of imposing import and export duty have been explained. The influence of a duty on the price of imported goods has been substantiated. The indicators of receipt of customs payments to the budget have been analyzed. The main trading partners of Ukraine have been identified. The peculiarities of administration of consumption taxes in the EU countries have been studied. Measures to increase the effectiveness of a customs duty and enhance its social role have been proposed. It has been proved that the customs-tax policy in the field of taxation of consumption should be flexible and should take into account the peculiarities of socio-economic development and the condition of the consumer market in Ukraine. Conclusion. Nowadays Ukraine’s foreign trade is partially approximated to the world standards. However, there is a need to improve the current system of taxation of export and import operations in order to save time during customs clearance of goods, to reduce differences between customs procedures in various countries of the world as well as to preserve the resources of state bodies and foreign economic entities. The conducted research has shown that today the following priorities are urgent for Ukraine: to combine existing systems of export control, import control and transit control into a single system; to provide foreign economic operators with the possibility to use places of a single electronic access for registration of foreign economic transactions; introduce a system of unified accounting of merchants with the registration only in one country; to provide foreign economic operators with the opportunity to use places of a single electronic access for registration of foreign economic transactions